Leukocytospermia and sperm preparation - a flow cytometric study - Perticarari Sandra; Simeone Roberto; Presani Gianni; Ricci Giuseppe; Boscolo Rita; Martinelli Monica; Fischer-Tamaro Leo; Guaschino Secondo (BMC, 2009)
Abstract Background Leukocytes represent the predominant source of reactive oxygen species both in seminal plasma and in sperm suspensions and have been demonstrated to negatively influence sperm function and fertilization rate in assisted reproduction procedures. Peroxidase test is the standard method recommended by WHO to detect semen leukocytes but it may be inaccurate. The aims of this study were (i) to compare the efficiency of swim-up and density-gradient centrifugation techniques in removing seminal leukocytes, (ii) to examine the effect of leukocytes on sperm preparation, and (iii) to compare flow cytometry and peroxidase test in determining leukocyte concentration in semen using a multiparameter flow cytometric method. Methods Semen samples from 126 male partners of couples undergoing infertility investigations were analyzed for leukocytospermia using standard optical microscopy and flow cytometry. Sixty-nine out of 126 samples were also processed using simultaneously the swim-up and density-gradient centrifugation techniques. A multiparameter flow cytometric analysis to assess simultaneously sperm concentration, sperm viability, sperm apoptosis, and leukocyte concentration was carried out on neat and prepared sperm. Results Both sperm preparation methods removed most seminal leukocytes. However, the concentration of leukocytes was significantly lower after swim-up compared to that after density-gradient centrifugation preparation. Leukocytes concentration, either initial or in prepared fractions, was not correlated with sperm parameters (optical microscopy and flow cytometry parameters) after semen processing. There was no correlation between leukocyte concentration in the ejaculate and sperm recovery rate, whereas a significant correlation was found between the concentration of the residual leukocytes in prepared fractions and viable sperm recovery rate. Although the overall concordance between the flow cytometry and the optical microscopy was satisfactory, the sensitivity of peroxidase test for the detection of leukocytospermia resulted low. Conclusion Seminal leukocytes do not seem to influence sperm preparation results. However, for assisted conception, semen samples containing leukocytes should be processed using swim-up method. Although peroxidase-test is recommended by WHO as the standard method for determining semen leukocytes, it should not be used in clinical research study.